RESEARCH ON THE AXIAL CARRYING CAPACITY OF ANGULAR CONTACT BALL BEARINGS BASED ON COMBINED LOADS - YAN Cheng; ZHANG YueChun; WANG Wen; LI Min; ZHANG Yong (Jixie qiangdu)
Aim at difficulty to calculate the angular contact ball bearings’ axial carrying capacity in combined loads,considering the different of every roller suffered load and the actual contact angle,using deformation coordination principle and Hertz contact theory,the critical condition is that the actual contact angle is not exceed the safety contact angle,which any roller contact ellipse is not truncated. According to the above-mentioned and basing on a general algorithm of axial carrying capacity subjected to pure axial load,this paper proposed the improved algorithm to calculate the axial carrying capacity in combined loads. Relying on professional software analyzing,the improved algorithm has been well validated,and it is of engineering significance. Using the SKF 7316 BECBM bearing as an example,the above two algorithms are compared and analyzed. The results showed that: The radial load will make axial carrying capacity of angular contact ball bearing appropriately increase. The bending moment will make it significantly reduced,and with the increase of bending moment,the carrying capacity of axial load decreases faster. Compared with the radial load,bending moment is the dominant factor in changing of axial carrying capacity.